Analgesic Effects of Magnesium Sulphate In Patients Undergoing Laparoscopic Cholecystectom - Yaseen, Talha; Rizvi, Syed Ali Mazhar; Mahmood, Khalid; Malik, Usman Eijaz; Aziz, Majid; Khan, Abid (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the effectiveness of intraoperative administration of MgSO4 in achieving satisfactory postoperative pain relief following laparoscopic surgery. Study Design: Quasi-experimental research. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, Apr to Sep 2021. Methodology: A total of 200 patients gave their informed consent before being split into two groups of 100. Patients were given Tablet Alprazolam 0.25mg and Omeprazole 20mg the night before surgery and again on the morning of surgery, and were asked for NPO for 8 hours before to surgery. Group 1 got 50 mg/kg of magnesium sulphate diluted in 250 ml of isotonic 0.9% normal saline intravenously during surgery, while Group 2 received the same volume of isotonic 0.9% normal saline. Results: Administering intravenous magnesium sulphate at an intravenous dose of 50 milligrams per kilogram of body weight before laryngoscopy and intubation significantly reduces the need for post-operative pain medication by reducing post-operative pain and delaying its onset. Additionally, it reduces the amount of pain medication required after surgery. Therefore, overall, pretreatment with magnesium sulphate has a significant impact on post-operative pain management. Conclusion: Magnesium sulphate is an excellent analgesic for people undergoing laparoscopic cholecystectomy.